Penerapan Permainan Tradisional Sambil Belajar untuk Perkembangan Sosial Anak Usia Sekolah Dasar - Samel Sopakua; Novita L. Sahertian; Arby William Mamangsa; Niken Revallo; Penta Astari Prasetya; Elvia Lelapary; Jidon Remas (Abdimas Universal, 2024)
This article describes the application of traditional games while learning for the social development of school-aged children. The aim of traditional games while learning is to help children's social development with various motor skills. Community Service (PkM) activities are focused on Mangga Dua hamlet, a remote, disadvantaged, poor area and aspects of education that have not been touched by services. For some children who have not enjoyed a good education because school buildings are not yet available, the distance to the educational location is approximately three kilometers to the main village of Saunulu, Tehoru District. There are some parents, and their children don't know how to read and write, they are still illiterate (literate). It is hoped that through this activity there will be awareness among parents to send their children to school even though they are faced with limited economic conditions and transportation. Through the implementation of traditional games while learning, it is hoped that culture can be preserved because it is full of moral values and social ethics. The method used is learning assistance while playing. PkM activities were carried out for three days. The community service activities carried out received responsiveness from all children and parents.